2012
DOI: 10.1002/art.34443
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidic acid receptor 1 suppression sensitizes rheumatoid fibroblast‐like synoviocytes to tumor necrosis factor–induced apoptosis

Abstract: Objective. To investigate the role of lysophosphatidic acid (LPA) receptors in the proliferation and apoptosis of fibroblast-like synoviocytes (FLS) from patients with rheumatoid arthritis (RA).Methods. Expression of LPA receptors 1-3 was analyzed by real-time polymerase chain reaction (PCR). LPAR1 and LPAR2 were suppressed in RA FLS by small interfering RNA (siRNA) transfection. Proliferation of RA FLS after tumor necrosis factor (TNF) and LPA stimulation was determined with a luminescent cell viability assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 47 publications
2
26
0
Order By: Relevance
“…Moreover, the expression of six G-protein-coupled LPA receptors increases in RA FLS. Thus, LPAs appear to function as lipid mediators between cells displaying growth factor-like activities [44]. We noted elevated levels of all PA and LPA species in SF of RA and OA compared with control SF, consistent with previous findings [45].…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, the expression of six G-protein-coupled LPA receptors increases in RA FLS. Thus, LPAs appear to function as lipid mediators between cells displaying growth factor-like activities [44]. We noted elevated levels of all PA and LPA species in SF of RA and OA compared with control SF, consistent with previous findings [45].…”
Section: Discussionsupporting
confidence: 91%
“…However, expression of other important inflammation markers was similar in Ki16425-treated and control mice indicating that regulation of inflammation is not the unique or main mechanism involved. This interpretation is in line with our previous data in human FLS 26. However, we cannot exclude that changes in expression of inflammatory mediators were more important than detected because the impossibility of isolating synovial tissue led to inclusion of other joint tissues, which likely decreased sensitivity to changes restricted to the synovium.…”
Section: Discussionsupporting
confidence: 90%
“…We previously demonstrated that suppression of LPA 1 receptor in RA FLS sensitises these cells to TNF-induced apoptosis by upregulation of TRAIL, TRADD and PYCARD 26. Now, we showed that blockade of LPA 1 receptor in mice increased apoptosis in arthritic joints and was accompanied by enhanced expression of TRADD and PYCARD.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations